Methods of Examining The Nature-Man Relationship in Warsaw Regional Geography - Walewski Andrzej (Miscellanea Geographica: Regional Studies on Development, 2006)
Several methods applied in the Department of Regional Geography of Warsaw University in research on the relationship between the natural environment and man were presented: chi-squared test, class diversification method, correlation methods, regression analysis. Their merits and limitations were described. The usefulness for research of different aspects of the nature-man relationship was discussed. New possibilities of applying thus obtained results (e.g. for delimitation of regions of the nature-man relationship) were identified.